1997
DOI: 10.4319/lo.1997.42.5_part_2.1178
|View full text |Cite
|
Sign up to set email alerts
|

Toxin variability during the cell cycle of the dinoflagellate Alexandrium fundyense

Abstract: Cultures of the toxic dinoflagellate AlexandriumfundyenseBalech were subjected to conditions that induced two synchronized divisions over a period of 48 h. Before, during, and after this in:erval, toxin content, toxin composition, and several other physiological parameters were monitored every 2 h for 94 h. Toxin production was discontinuous, induced by light, and always occurred during a defined time frame within Ihe G, phase of the cell cycle. Specific toxin production rates were positive for a period of -8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(115 citation statements)
references
References 29 publications
7
106
1
Order By: Relevance
“…DD of mRNA was applied to synchronized cells of A. fundyense in different cell cycle stages (Fig. 2B) and while toxin production was on or off (52). Two samples were drawn during G 1 , one while toxin production was active (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DD of mRNA was applied to synchronized cells of A. fundyense in different cell cycle stages (Fig. 2B) and while toxin production was on or off (52). Two samples were drawn during G 1 , one while toxin production was active (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A series of studies with synchronized cultures of Alexandrium fundyense has further shown that STX is accumulated during a discrete time period localized in the G 1 phase of the cell cycle ( Fig. 1) (52). The combination of these two factors, nuclear genes and discontinuous toxigenesis, gave rise to the hypothesis that STX biosynthesis could be regulated at the transcriptional level, with the genes responsible for toxin production being activated in a cyclic pattern.…”
mentioning
confidence: 99%
“…In this case, the DD patterns were identical for G 1 , S, and G 2 phases, which permitted the identification of differentially expressed bands. Saxitoxin has been shown to accumulate during a discrete time period in the G1 phase of the cell cycle (Taroncher-Oldenburg et al, 1997). Thus, the focus was to identify genes expressed or suppressed in early G 1 when compared with the remainder of the cell cycle.…”
Section: Current Methods For Isolating Dinoflagellate Genesmentioning
confidence: 99%
“…Therefore, toxin composition has been used as a chemotaxonomic character that distinguishes isolates of Alexandrium from different geographic regions . Only recently have changes in Alexandrium toxin composition been observed during growth in batch culture (late stationary phase) ), over the cell cycle and in N-and P-limited semi-continuous cultures (Anderson et al 1990b;Taroncher-Oldenburg et al 1997). …”
Section: Allocation Of Carbon and Nitrogenmentioning
confidence: 99%